Shyama Sangeeter Bhakti Sudhay Kazi Nazrul Islam - Sarker, Asha (Jagannath University Journal of Arts, 2026)
Kazi Nazrul Islam is one of the legendary writers in Bengali literature and music as well as cultural arena. His creative and exceptional merit enriches Bengali literature and music. He was totally free from orthodoxy and narrowness by his merit and wisdom that made him a poet of mass people and humanity. He composed a lot of lyrical music that was full of love, affection, emotion as well as rebellion to the authoritarianism. He also composed a lot of Hindu devotional songs on goddess Kali without considering his religion, race and community. In these devotional songs goddess Kali was emerged somewhere as affectionate mother or daughter else somewhere as homeland on divine feminine energy. Nazrul was highly inspired in this genre named Shyama Sangeet by Ramprasad Sen, a devoted Shakta poet to address Kali with such intimate devotion. Furthermore, the then anti-British nationalistic sense of people simultaneously reached the Nazrul’s Shyama Sangeet in highest peak. The diversity, variety and eternal beauty of Shyama Sangeet is revealed in this journal in an aesthetic way. Through textual analysis and comparative research methodology, this research manifests of Kazi Nazrul Islam’s simple and rhythmical thought and creation of Shyama Sangeet. Jagannath University Journal of Arts, v-15, i-01, 2025:p65-74